Scleral buckle is good option for treatment of uncomplicated retinal detachment Introflexão escleral é boa opção para tratamento de descolamento de retina não complicado - Iuuki Takasaka (Revista Brasileira de Oftalmologia, 2012)
OBJETIVE: To describe the reattachment rate and visual acuity results of patients with uncomplicated rhegmatogenous retinal detachment who underwent segmental scleral buckle surgery. METHODS: Prospective case series of 100 patients with visual loss or symptoms (floaters and photopsia) of less than 30 days' duration scheduled for surgery. No patient had a retinal break greater than 30°, a retinal detachment larger than 2 quadrants or proliferative vitreoretinopathy. RESULTS: The 1-week, 1-month, and 6-month anatomical success rates were 93%, 100%, and 100%, respectively. Seven patients underwent one additional retinal detachment surgery (pars plan vitrectomy) after primary failure at 1-week follow-up. The preoperative, 1-month, and 6-month best correct visual acuity were 20/100, 20/80, and 20/50, respectively. The postoperative complications were: eyelid edema in 10% of the patients, transient ocular hypertension in 5%, macular pucker in 3%, transient diplopia in 3%, and hyphema (<0.5mm) in 1%. CONCLUSION: In patients with uncomplicated retinal detachment, segmental scleral buckle showed a very good anatomical and functional success, with a few number of major complications. OBJETIVO: Descrever a taxa de reaplicação e os resultados da acuidade visual dos pacientes com descolamento de retina regmatogênico simples que se submeteram à cirurgia de introflexão escleral segmentar. MÉTODOS: Uma série de casos prospectivo de 100 pacientes com perda visual ou sintomas (floaters e fotopsia), com duração inferior a 30 dias, agendados para a cirurgia. Nenhum paciente apresentou uma ruptura da retina superior a 30°, um descolamento de retina maior que 2 quadrantes ou vitreorretinopatia. RESULTADOS: As taxas de sucesso anatômico em 1 semana, 1 mês e 6 meses foram de 93%, 100% e 100%, respectivamente. Sete pacientes foram submetidos à cirurgia de descolamento de retina adicional (vitrectomia via pars plana) após falha primária em uma semana de seguimento. A melhor acuidade visual pré-operatória, 1 mês, e de 6 meses pós-operatório foram 20/100, 20/80 e 20/50, respectivamente. As complicações pós-operatórias foram: edema palpebral em 10% dos pacientes, a hipertensão ocular transitória em 5%, pucker macular em 3%, diplopia transiente em 3%, e hifema (<0,5 mm) em 1%. CONCLUSÃO: Em pacientes com descolamento da retina sem complicações, a cirurgia de introflexão segmentar escleral mostrou um sucesso anatômico e funcional muito bom, com um número menor de complicações maiores.